COVID-19 and Labour Law: U.S. - Bales, Richard; Elko, Christopher (Italian Labour Law e-Journal, 2020)
Since the initial response to the Covid-19 labor crisis, the United States has faced a series of issues that raise questions as to the success of the initial measures taken, as well as the potential need for future legislation. Just as the United States took a piecemeal approach to shutting down, it has taken the same approach to reopening. With political pressure mounting to reopen the economy in full, parts of the U.S. are in medical crisis and many legal issues remain to be addressed.